2016
DOI: 10.17711/sm.0185-3325.2016.034
|View full text |Cite
|
Sign up to set email alerts
|

Traducción al español de la escala de adicción a los alimentos de Yale (Yale Food Addiction Scale) y su evaluación en una muestra de población mexicana. Análisis factorial

Abstract: Discussion and conclusionThe Spanish version of the YFAS showed psychometric properties not different from the original and adapted existing versions. Therefore, YFAS Spanish version could be useful in healthcare and clinical research in Mexican population.Key words: Obesity, addictive behavior, validation study. RESUMEN IntroducciónLa obesidad es la acumulación excesiva de grasa corporal, lo que condiciona una alta comorbilidad. El consumo descontrolado de alimentos hipercalóricos es causa de su desarrollo; é… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…In this way, the full scale presented here meets the established criteria for the diagnosis of substance addictions, which supports its use [7][8][9]32]. This is similar to what was found in a study where a factorial analysis of a Spanish translation of the YFAS was performed in a Mexican sample [40]. Five factors were found, which include those encountered in this study and with the YFAS itself [19], where four factors were found.…”
Section: Discussionsupporting
confidence: 85%
“…In this way, the full scale presented here meets the established criteria for the diagnosis of substance addictions, which supports its use [7][8][9]32]. This is similar to what was found in a study where a factorial analysis of a Spanish translation of the YFAS was performed in a Mexican sample [40]. Five factors were found, which include those encountered in this study and with the YFAS itself [19], where four factors were found.…”
Section: Discussionsupporting
confidence: 85%
“…Since the development of the Yale Food Addiction Scale (YFAS) psychometric scale to measure FA, several studies have been conducted on this theme worldwide (Davis, 2017; Praxedes et al, 2022; Pursey et al, 2014). The scale has been translated and validated into Brazilian Portuguese (Nunes‐Neto et al, 2018) and Spanish (Granero et al, 2014; Granero et al, 2018), including with semantic adaptations for the Chilean (Marín, 2014) and Mexican populations (Valdés‐Moreno et al, 2016), and some studies using this scale have thus reported on the prevalence of FA in Latin American countries (Falcón et al, 2021; Filgueiras et al, 2019; Lopez‐Lopez et al, 2021; Obregón et al, 2015). However, to date, prevalence of FA in Latin American populations has not been systematically investigated, which is an important gap given the specificities of this group.…”
Section: Introductionmentioning
confidence: 99%
“…También permite discriminar entre individuos con TPA moderado o severo e individuos sin este trastorno. En esta investigación se empleó la validación mexicana de Moreno et al (2016) dadas sus adecuadas propiedades psicométricas (valor del α de Cronbach de 0.7963). Para la confiabilidad se obtuvo el coeficiente de Spearman por la metodología test-retest, de r = 0.565.…”
Section: Escala De Adicción a La Comida De Yale (Yfas)unclassified